ANALISIS PENGARUH PEMASANGAN FILTER HARMONISA PADA INVERTER 3 FASA SEBAGAI KONTROL MOTOR BRUSHLESS DC MENGGUNAKAN POWER SIMULATOR - Faldin; Samuel Jie; St. Nawal Jaya; Mustarum Musaruddin; Hasmina Tari Mokui; Achmad Nur Aliansyah; Mansur (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2023)
Abstract â€” Electric vehicles are vehicles that use electric motors as their power source. The most suitable type of DC motor for electric vehicles is the Brushless DC motor. BLDC motors require a 3-phase power source from an inverter to operate. A good inverter is one that has a THD value of less than 5%. To eliminate THD values in the inverter, an LC harmonic filter can be used. The purpose of this study is to analyze the effect of using an LC filter on the voltage, current, and Total Harmonic Distortion (THD) values in a 3-phase inverter. The method used is a literature review, creating a simulation circuit in PSIM software, and analyzing the simulation results under no-load and load conditions. The simulation results without an LC filter under a load of 1.47 Nm showed a voltage value of 100 V, current of 4.6 A, input power of 460 W, output power of 417.61 W, BLDC motor speed of 2697 rpm, motor efficiency of 90.2%, and THD voltage of 2.36% and THD current of 6.50%. After installing the L 34.84 mH and C 85ÂµF filter in the circuit, the results showed a voltage value of 100 V, current of 4.3 A, input power of 430 W, output power of 409.72 W, BLDC motor speed of 2646 rpm, motor efficiency of 95.3%, and THD voltage of 1.51% and THD current of 3.99%. The conclusion of this study is that the use of an LC filter reduces THD values to below 5% or meets IEEE standards, allowing the inverter and BLDC motor to operate more optimally.